Prenatal diagnosis of short-rib polydactyly syndrome type III or short-rib thoracic dysplasia 3 with or without polydactyly (SRTD3) associated with compound heterozygous mutations in DYNC2H1 in a fetus - Chih-Ping Chen; Tsang-Ming Ko; Tung-Yao Chang; Schu-Rern Chern; Shin-Wen Chen; Shih-Ting Lai; Tzu-Yun Chuang; Wayseen Wang (Elsevier, 2018)
Objective: We present the perinatal imaging findings and molecular genetic analysis in a fetus with short-rib polydactyly syndrome (SRPS) type III or short-rib thoracic dysplasia 3 with or without polydactyly (SRTD3). Case report: A 29-year-old, primigravid woman was referred for genetic counseling at 15 weeks of gestation because of abnormal ultrasound findings of short limbs, a narrow chest and bilateral polydactyly of the hands and feet, consistent with a diagnosis of SRPS type III. Chorionic villus sampling was performed, and targeted next-generation sequencing (NGS) was applied to analyze a panel of 25 genes including CEP120, DYNC2H1, DYNC2LI1, EVC, EVC2, FGFR2, FGFR3, HOXD10, IFT122, IFT140, IFT172, IFT52, IFT80, KIAA0586, NEK1, PAPSS2, SLC26A2, SOX9, TCTEX1D2, TCTN3, TTC21B, WDR19, WDR34, WDR35 and WDR60. The NGS analysis identified novel mutations in the DYNC2H1 gene. The fetus was compound heterozygous for a missense mutation c.8077G > T (p.Asp2693Tyr) of paternal origin in DYNC2H1 and a frameshift mutation c.11741_11742delTT (p.Phe3914X) of maternal origin in DYNC2H1. The fetus had a karyotype of 46,XY, and postnatally manifested characteristic SRPS type III phenotype. Conclusion: Targeted NGS is useful in genetic diagnosis of fetal skeletal dysplasia and SRPS, and the information acquired is helpful in genetic counseling.